ECG Quiz 43 Answer - Milla, Rob Scott; Chin, Ashley (SA Heart Journal, 2017)
This is a regular wide QRS tachycardia at 144 bpm (6 x 24). The QRS in V1 is positive, resembling RBBB and there are sharp deflections at the end of the T wave, suggesting atrial activity.